MODEL OF ENTREPRENEURIAL MARKETING ON WOMENPRENEUR - Aldina Shiratina; Yanto Ramli; Nia Kusuma Wardhani; Nandan Limakrisna (Dinasti International Journal of Education Management And Social Science, 2020)
This research revealed the model of entrepreneurial marketing, especially on Moslem fashion womenpreneurs. Recently, the opportunity for women in entrepreneurship with micro and small scale businesses (MSMEs) has increase. Womenpreneur also contributes to the field of human resource management, namely empowering women and playing a role in the nation's economy. The main reason is that they want to be independent, followed by the second rank who says that opening a business, especially the Moslem fashion business, as an effort to increase family income. Implementing the concept of entrepreneurial marketing requires supporting factors, namely market orientation, innovation, value creation, and risk-taking. The purpose of this research is to implement the model of entrepreneurial marketing on womenpreneurs. This research used a descriptive survey method through SEM (Structural Equation Models) analysis. Sample of this research is 209 Moslem fashion womenpreneurs with a small business scale in West Java from different characteristics, both shar'i Moslem fashion (veiled), semi-shari'a and trendy. This research has been reduced the dimensions of previous studies, only focus on market orientation, innovation, and value creation, without risk-taking factors because womenpreneurs have been thinking first before they start the business and they have calculated risk factors. that value creation can be formed from market orientation and innovation. As we can say, market orientation and innovation are important factors in the formation of value creation for women entrepreneurs of small scale Moslem fashion in West Java By applying these concepts, it builds an effective entrepreneurial marketing performance for womenpreneur.